“I HAD BECOME A COW”: KIMURA YŪSUKE’S "SACRED CESIUM GROUND" AND ROBERT MOORE’S "FIGURING GROUND" - Shoshannah GANZ (Studia Universitatis Babeş-Bolyai. Philologia, 2022)
“I had become a cow”: Kimura Yūsuke’s Sacred Cesium Ground and Robert Moore’s Figuring Ground. This paper shows how Kimura Yūsuke’s Sacred Cesium Ground (2016; translated 2019) and Robert Moore’s Figuring Ground (2009) expose the biopolitical manipulation of humans and animals thereby demonstrating the possibility of transcending narrow species boundaries. These authors both employ literary techniques such as humorous absurdism, embracing madness, and cultivating activism, while at the same time engaging with the ethical questions raised by critical animal studies. Of particular importance for the comparative discussions of Kimura and Moore’s texts will be Donna Haraway’s identification of herself as a philosopher of the “mud” and her derision of the philosophy of the “sky” or the abstraction employed by Deleuze and Guattari. This paper likewise employs Carol J. Adams’s ideas of the shared absent referent in meat eating and pornography and the development on this thought in Nicole Shukin’s theory of rendering. This paper moreover draws attention to the rupture created through the violence of the slaughterhouse and the slaughter of cattle following 3/11 in Japan to show the suffering of animals and the necessity of acknowledging the shared experience of species. Robert Moore’s Figuring Ground and Kimura Yūsuke’s Sacred Cesium Ground thus allow for the movement from the historical capitalist preoccupation with cattle as commodity to an understanding of cows as part of a trans-species community.